Clinical Factors Predicting Voluntary Driving Cessation among Patients with Parkinson’s Disease - Hidetada Yamada; Masahiro Nakamori; Tomohisa Nezu; Teppei Kotozaki; Juri Kitamura; Tomohiko Ohshita; Yoshimasa Sueda; Hirofumi Maruyama (Behavioural Neurology)
Factors that influence the decision of voluntary driving cessation in patients living with Parkinson’s disease (PD) are still unclear. We aimed to reveal the factors affecting the decision of voluntary driving cessation in patients with PD. This hospital-based cross-sectional study recruited consecutive outpatients with PD. Data on sociodemographic and clinical characteristics and medication use were collected from the patients using semistructured interviews. Cognitive function was evaluated using the Japanese version of the Montreal Cognitive Assessment (MoCA-J). We excluded patients with dementia or motor impairment (Hoehn−Yahr stage>3). We divided the patients into two groups, with and without voluntary driving cessation (D: driver; RD: retired driver), and conducted investigations using multivariate logistic regression analyses. Of the 40 patients, 8 (20.0%) voluntarily retired from driving. Patients who decided on driving cessation had a higher prevalence of freezing of gait (FOG) (D vs. RD, 25.0% vs. 87.5%; P=0.001) and tended to have lower scores for attention in the MoCA-J (D vs. RD, 5.0±1.2 vs. 4.1±1.4; P=0.086). Multivariable analysis showed that FOG was independently associated with driving cessation (odds ratio: 14.46, 95% confidence interval: 1.91–303.74). FOG was associated with voluntary driving cessation in patients with PD without dementia or severe motor impairment. Physicians should consider providing extensive social support to maintain patients’ mobility and independence, especially if the patients have these clinical factors.